2023
DOI: 10.3389/fcimb.2023.1121186
|View full text |Cite
|
Sign up to set email alerts
|

The phylogeny and distribution of Wolbachia in two pathogen vector insects, Asian citrus psyllid and Longan psyllid

Abstract: BackgroundWolbachia is the most abundant bacterial endosymbiont among insects. It can play a prominent role in the development, reproduction and immunity of its given insect host. To date, Wolbachia presence is well studied within aphids, whiteflies and planthoppers, but relatively few studies have investigated its presence in psyllids.MethodsHere, the infection status of Wolbachia in five species of psyllid, including Asian citrus psyllid Diaphorina citri and longan psyllid Cornegenapsylla sinica was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
1
1
0
Order By: Relevance
“…16S rRNA high-throughput sequencing suggested that the intracellular bacteria endosymbiont Wolbachia was found in the ovaries and salivary glands of S. frugiperda female adults. Moreover, our results are similar to the findings of a previous study by Ou et al [73], in which Wolbachia was detected in the midgut, salivary glands, testes, and ovaries of Diaphorina citri (Hemiptera: Psyllidae) and Cornegenapsylla sinica (Hemiptera: Psyllidae). To date, approximately 80% of lepidopteran insects are estimated to be infected by Wolbachia [74].…”
Section: Discussionsupporting
confidence: 92%
“…16S rRNA high-throughput sequencing suggested that the intracellular bacteria endosymbiont Wolbachia was found in the ovaries and salivary glands of S. frugiperda female adults. Moreover, our results are similar to the findings of a previous study by Ou et al [73], in which Wolbachia was detected in the midgut, salivary glands, testes, and ovaries of Diaphorina citri (Hemiptera: Psyllidae) and Cornegenapsylla sinica (Hemiptera: Psyllidae). To date, approximately 80% of lepidopteran insects are estimated to be infected by Wolbachia [74].…”
Section: Discussionsupporting
confidence: 92%
“… 42 The Wolbachia strains discovered in psyllid species to date all belong to supergroup B. 43 , 44 Due to its limited capacity for amino acid biosynthesis, Wolbachia supergroups A and B have been traditionally known to be highly dependent on the amino acid metabolism of its hosts, 45 , 46 while recent studies have provided evidence of evolutionary transitions from facultative to obligate mutualisms in certain members of the Wolbachia F supergroups. 47 , 48 Here higher genome copy counts of Wolbachia were measured in D. citri and B. cockerelli bacteriomes compared to body tissues ( Figure 5 ), suggesting that Wolbachia may have direct metabolic influences on the host and obligate symbiont(s) within bacteriomes for amino acids.…”
Section: Discussionmentioning
confidence: 99%